Validation of a modified three-day weighed food record for measuring energy intake in preschool-aged children with cerebral palsy - Walker, J.; Bell, K.; Boyd, Roslyn; Davies, P. (2013)
Background & aims: Accurate energy intake (EI) determination in children with cerebral palsy (CP) is critical for nutritional management, however no valid measures exist. We aimed to validate a modified three-day weighed food record for measuring EI in preschool-aged children with CP. Methods: Thirty-one children with CP (61% male) of all functional abilities and 15 typically developing children (TDC) (63% male), median age 3.79 years participated. A three-day weighed food record was validated by comparing reported EI to measured total energy expenditure (TEE) via doubly labelled water, assuming a state of weight balance. Results: Children with moderate-severe CP showed no difference between EI and TEE. Values for EI were less than TEE in children with mild CP and TDC (p < 0.01, limits of agreement -2559 to 845 kJ and -2524 to 350 kJ respectively). The mean difference between EI and TEE as a percentage of measured TEE was 14.8% (mild CP), 4.3% (moderate-severe CP) and 16.8% (TDC), all less than data detailing typical within-subject variability in day-to-day EI. Conclusions: In contrast to previous literature, results demonstrated that a modified three-day weighed food record accurately measured EI in preschool-aged children with CP. This record can be used in clinical practice and future research to accurately determine EI in this population. © 2012 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism.